PERAN MUSEUM DAERAH KLATEN DALAM MEMPERTAHANKAN BUDAYA MASYARAKAT DI ERA DIGITAL - Naya Amalia; Nabilla Fikriani; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The purpose of this study is to explain the role of the Klaten Regency Regional Museum in preserving community culture in the digital era, focusing on cultural preservation activities, the use of digital technology, and the challenges faced. This research uses a qualitative method with a descriptive approach. The data collection techniques employed include interviews, observation, and documentation. To support the research, the researcher also uses literature studies, utilizing relevant information related to the research theme. The results of this study show that the Klaten Regency Regional Museum not only preserves artifacts and cultural heritage but also serves as a space for education and innovative cultural interaction through collection digitization, social media promotion, and community-based educational programs. The use of social media and digitized collections has improved public access to cultural information, increased awareness of cultural preservation, and strengthened local identity in the modern era. However, the museum also faces challenges such as limited resources, staff unfamiliar with technology, and difficulties in capturing the interest of the younger generation.